Trigonometric-series solution for analysis of laminated composite beams. (15th January 2017) - Nguyen, Trung-Kien; Nguyen, Ngoc-Duong; Vo, Thuc P.; Thai, Huu-Tai
Abstract: A new analytical solution based on a higher-order beam theory for static, buckling and vibration of laminated composite beams is proposed in this paper. The governing equations of motion are derived from Lagrange's equations. An analytical solution based on trigonometric series, which satisfies various boundary conditions, is developed to solve the problem. Numerical results are obtained to compare with previous studies and to investigate the effects of length-to-depth ratio, fibre angles and material anisotropy on the deflections, stresses, natural frequencies and critical buckling loads of composite beams with various configurations.